2021
DOI: 10.1039/d0lc01009j
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic channel integrated with a lattice lightsheet microscopic system for continuous cell imaging

Abstract: In this study, a continuous cell imaging system with subcellular resolution by integrating a microfluidic platform with lattice lightsheet microscopy (LLSM) was developed. To reduce aberrations of the lightsheet propagating...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…It is also important to consider the physiological implications of the findings to better understand cell differentiation and function. Since only limited research has combined light‐sheet imaging with microfluidics, further studies may investigate the sequence and timing of cell motion during chemokine sensing and continual migration 165 . The current microfluidic devices can somewhat mimic the diffusive gradients of one or two soluble chemokines.…”
Section: Outlook and Future Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to consider the physiological implications of the findings to better understand cell differentiation and function. Since only limited research has combined light‐sheet imaging with microfluidics, further studies may investigate the sequence and timing of cell motion during chemokine sensing and continual migration 165 . The current microfluidic devices can somewhat mimic the diffusive gradients of one or two soluble chemokines.…”
Section: Outlook and Future Applicationsmentioning
confidence: 99%
“…Since only limited research has combined light-sheet imaging with microfluidics, further studies may investigate the sequence and timing of cell motion during chemokine sensing and continual migration. 165 The current microfluidic devices can somewhat mimic the diffusive gradients of one or two soluble chemokines. However, as chemokine binding to GAGs or other extracellular matrix molecules changes the way immune cells sense and migrate toward a gradient, this may lead to different chemotactic preferences and cytoskeletal modifications.…”
Section: Outlook and Future Appli C Ati On Smentioning
confidence: 99%
“…Second, the refractive index of PDMS does not match the refractive index of the aqueous growth media, which would result in unacceptable optical aberrations. , Because of these challenges, LLSM-integrated microfluidic channels are rare. Only very recently, Fan et al reported an LLSM-integrated channel sealed with Sarstedt Lumox film, a biocompatible material that has a refractive index similar to water . However, repeated high-resolution imaging of living cells over time was not possible because the numerical aperture (NA) of that imaging system was 0.8 (the imaging system used here has an NA of 1.1), and the channel was not mounted on a motorized sample stage which would enable imaging of large specimen volumes by stage scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we see that that most work is being focused on techniques and methods that can rapidly and easily detect candida non-invasively, and that can offer a high sensitivity and accuracy to match the current gold standard in the field, which is culturing cells taken from blood samples. Other novel biosensing techniques, e.g., Brownian nanobeads [31][32][33][34][35], surface plasmon resonance [36], liquid crystal [37,38], nano-gold clusters [39], and flow cytometers [40][41][42], can also be the potential techniques for Candida detection.…”
Section: Introductionmentioning
confidence: 99%